Issues and Challenges in Diagnoses of Borderline Ovarian Neoplasms by Frozen Section - Sarma, Usha; Das, Navanita; Phukan, Neeharika (Asian Pacific Journal of Cancer Biology, 2023)
Introduction: Frozen section is a rapid intraoperative method of tissue sectioning with the help of cryostat to arrive at a diagnosis and guide the operative procedure. It is an important diagnostic tool in the intraoperative management of ovarian neoplasms. Aims and Objectives: 1) To evaluate clinically suspected ovarian neoplastic lesions by frozen section. 2) To analyze the factors associated with difficulty in diagnoses of borderline ovarian neoplasms. Materials and Methods: This is a cross-sectional study conducted in the Department of Pathology for a period of 2 years. 60 cases of ovarian neoplasms undergoing Frozen section and subsequent histopathological examination are included in the study. Results: The mean age of patient is 39.49 years (21-72). Of the 60 cases, 73.33% are benign, 8.33% borderline and 18.3% are malignant on histopathological diagnosis. The concordance rate of frozen section with histopathological diagnosis is 91.67%. The sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of Frozen section in the diagnosis of Benign, Borderline and Malignant ovarian neoplasms are 95.45%, 92.73%, 97.67%, 88.24% and 88.64%; 100%, 92.16%, 55.56%, 100% and 55.56%; 72.73%, 100%, 100%, 94.23% and 72.73% respectively. Conclusion: Frozen section of ovarian neoplasms helps to arrive at a diagnosis of whether they are benign or malignant with a high level of accuracy. Diagnosis of a benign lesion in a young patient guides the surgeon to a fertility conserving surgery. Likewise, diagnosis of a malignant lesion on table guides the surgeon to execute an extensive surgery in a single setting, saving the patient of the physical, emotional, psychological and financial strain of a second look operation.